Metal Oxide Sensors Applied to Industrial and Consumer Applications: Examples and Requirements for Successful Implementation - Debra J. Deininger (Proceedings, 2019)
Metal Oxide (MOx) sensors have been the subject of intense research and development over the years, and are widely used in industrial and commercial sensing applications [...]